Gestational diabetes mellitus is as innocent as you think? - Uysal, Gulsum; Kutuk, Mehmet Serdar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: We aimed to compare fetal outcomes, fetal hypoxia, acidemia and maternal chracteristics including hemoglobin A1c, doppler indices between gestational diabetes mellitus (GDM) and pregestational diabetes mellitus (DM) among pregnant women treated with insulin. Methods: Data of pregnant patients with diagnosis of pregestational diabetes (type 1 and 2) and GDM who were treated with insulin (GDM A2 in White classification) was retrospectively collected and compared. Patients with active chronic systemic disease, multiple pregnancies, lost to follow up and detected fetal malformations were exluded. Maternal characteristics, umbilical doppler indices and amnion fluid index, gestational age at delivery, delivery characteristics (including vaginal delivery, or cesarean section) and newborn characteristics such as birth weight, Apgar score and umblical cord pH were all recorded. Results: A total of 130 patients (67 patients with GDM and 63 pregestational DM) were recruited to the study. There were no significant difference regarding type of delivery, fetal birth weight, umbilical cord Hb and gestational birth age. No other significant difference in frequency of low Apgar scores and fetal acidosis or metabolic acidosis were reported. HbA1c and blood glucose levels and insulin dosage were significantly statistically higher in pregestational group. Conclusions: The frequency of fetal distress parameters and poor fetal outcome were similar between groups although pregestaional diabetic patients had higher HbA1c rates. Therefore, patients with GDM (A2) should be followed up as closely as pregestational (overt) diabetic patients.